Homoeologous crossovers are distally biased and underlie genomic instability in first-generation neo-allopolyploid Arabidopsis suecica - Nibau, Candida (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.